1985
DOI: 10.3177/jnsv.31.385
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fish protein, soybean protein and casein on cholesterol turnover in rats.

Abstract: SummaryThe effects of dietary fish, soybean protein and casein on cholesterol turnover were compared in rats. After the injection of [14C]cholesterol into the rats, the specific activities of radioactive choles terol in feces were followed for 4 weeks. The cholesterol half-lives calculated from the decay curves of the specific activities were 14.7 and 14.6 days in rats fed fish protein and soybean protein , respectively. These were shorter than the half-life (17.4 days) in casein-fed controls. The fish and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…These results are in good agreement with those previously observed in rats (15,36). However, in this study hepatic cholesterol in rats fed cod protein was significantly different, being intermediate to hepatic cholesterol in rats fed casein and soy protein.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in good agreement with those previously observed in rats (15,36). However, in this study hepatic cholesterol in rats fed cod protein was significantly different, being intermediate to hepatic cholesterol in rats fed casein and soy protein.…”
Section: Discussionsupporting
confidence: 93%
“…However, in this study hepatic cholesterol in rats fed cod protein was significantly different, being intermediate to hepatic cholesterol in rats fed casein and soy protein. Other studies in rats showed significantly higher hepatic cholesterol concentrations after cod protein feeding compared with soy protein feeding, but cod protein and casein did not induce statistically different effects in these studies (15,36). As with soy protein, it has been postulated that the lower lysine/arginine ratio of cod protein when compared with casein may have played a role in the hypocholesterolemic effect of cod protein (37).…”
Section: Discussionmentioning
confidence: 68%
“…In previous studies in rats, fish proteins have been found to decrease plasma TC concentration in comparison with casein. [10][11][12] Hypocholesterolemic effect of fish protein in rats 13 has been attributed to a decrease in liver cholesterol output into the circulation due to a stimulation of cholesterol to bile acid conversion and to increased excretion Fish intake and blood lipids during weight loss I Gunnarsdottir et al of cholesterol and its metabolites into faeces 37 or reduced activity of Acyl-CoA: cholesterol acyltransferace. 38 These observations suggest that fish proteins might have cardioprotective effect and be involved in the regulation of plasma cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…Many publications have reported that dietary soybean protein showed hy pocholesterolemic effects when compared with animal protein such as casein (1)(2)(3)(4)(5)(6)(7). However, the effects of soybean protein on triglyceride levels were not consistent in the publications and have not been so extensively investigated as the effects on cholesterol level.…”
mentioning
confidence: 99%